Electrochemical studies of lateral flow assay test results for procalcitonin detection - Yachana Gupta Gupta (International Association of Physical Chemists (IAPC), 2021)
In this study, the lateral flow assay (LFA) has been developed for the detection of bacterial infection (BI) by specific biomarker procalcitonin (PCT), without a need for complicated instrumentations and technical expertise. For the development of the assay, gold nanoparticles (AuNP) and their conjugates with antibodies specific to the model antigen PCT are assessed. Polyclonal antibody (pAb) labelled with gold nanoparticles (AuNP) to obtain the AuNP-pAb complex and the specific monoclonal antibody (mAb) have been dropped at the test zone. This complex is placed over the conjugate line of the LFA strip. In the absence of PCT or the presence of other biomarkers, the test line remained colourless, which revealed the specificity of assay towards PCT among a pool of various analytes. Herein, observations have been made through two different platforms for quantitative and qualitative analysis for the detection of PCT biomarker. The qualitative analysis has been performed on the basis of appearance red color in the test band, while for quantitative analysis, a novel approach has been adopted. Herein, the nitrocellulose membrane (paper strip) is cut out from the LFA strip and used for electrochemical studies under similar solution conditions. Different paper strips presented different cyclic voltammograms (CV) that could be correlated to varying PCT concentrations captured at the test line of the paper strip. The qualitative detection limit for PCT using this LFA was determined to be 2 ng/ml and the quantitative detection limit was 1 ng/ml. The electrochemical response studies of the paper strip by CV technique revealed the sensitivity value of 0.695 mA ng/ml.